(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Congenital diaphragmatic hernias are commonly symptomatic within 24 hours after birth, but late presentation is not uncommon. Late presentation of congenital diaphragmatic hernia poses diagnostic difficulties as clinical picture are vague, and more commonly presented with non-specific gastrointestinal and respiratory symptoms. Due to the vague and non-specific clinical presentation, clinician faces a diagnostic dilemma resulting in delay in diagnosis and many a times an inappropriate management. This article reports 2 cases of late-presenting congenital diaphragmatic hernia (over the period of 6 months from September 2014 to February 2015) in National Institute of Disease of Chest and Hospital (NIDCH). In first case, she was diagnosed as right-sided tubercular pleural effusion and was treated with CAT-1 anti-tubercular therapy for 6 months without any clinical improvement. Later CT scan of chest was done and diagnosed as a case of congenital diaphragmatic hernia. The second case was diagnosed as a left-sided hydropneumothorax and treated with left tube thoracostomy. During removal of the intercostal chest tube, some fatty tissue was pulled out of the thoracostomy site. In NIDCH, she was diagnosed as a case of diaphragmatic hernia by barium follow-through. Both cases were diagnosed as Bochdalek hernia during the repair of the hernia defect via thoracotomy.